Determination of TBT in water and sediment samples along the Argentine Atlantic coast - De Waisbaum, R. G. (2010)
Cases of imposex have been reported for some organisms living in areas of the Argentine Atlantic coast. Since this is one of the known effects of the anti-fouling agent tributyltin (TBT), quantitative determinations of organotins in samples of water and sediments collected from sites along the Argentine coast were carried out. Severe cases of imposex were first reported for two gastropod species living in the Mar del Plata area, and determinations of TBT in samples collected from this site gave extremely high values and showed a close correlation between the degree of imposex and TBT concentration. Recent investigations in the area have shown a significant decrease. Surveys were also conducted in sites that exhibit highly irregular coastal profiles to examine the relevance of physical environments. Alarming concentrations of TBT were determined in most of the sites where heavy boat traffic and/or marine activities occur, demonstrating the urgent need for regulations to avoid further input of TBT. Reports from other sites in South America reveal that this should be a subject of regional concern in order to avoid severe damage to the biodiversity of regional marine organisms.